Study of Carbon Storage in Mangrove Vegetation at Sumbernadi Village, Ketapang Distric, South Lampung Regency, Province of Lampung - Kusuma, Anma Hari (Jurnal Biologi Tropis, 2024)
Mangroves are typical plants that live in coastal areas that are affected by tides and are able to adapt to salinity. Mangroves are able to absorb and store carbon. The aims of this study to analyze carbon absorption in the mangrove vegetation of Sumbernadi Village. The research was conducted from June-July 2023 in Sumbernadi Village, Ketapang District, South Lampung, Province of Lampung. Mangrove carbon measurements in mangrove stands, necromass and litter were carried out using non-destructive methods. The carbon stored in sediment is greater than carbon stored in stands, necromass and litter. The highest carbon stored in sediment is in sediment that has coarse clay because coarse clay can store high levels of nutrients.